2013
DOI: 10.1371/journal.pone.0073247
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Importance of Steps Taken per Day among Persons with Multiple Sclerosis

Abstract: BackgroundThe number of steps taken per day (steps/day) provides a reliable and valid outcome of free-living walking behavior in persons with multiple sclerosis (MS).ObjectiveThis study examined the clinical meaningfulness of steps/day using the minimal clinically important difference (MCID) value across stages representing the developing impact of MS.MethodsThis study was a secondary analysis of de-identified data from 15 investigations totaling 786 persons with MS and 157 healthy controls. All participants p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 17 publications
4
45
0
Order By: Relevance
“…The number of steps taken per day was previously shown to provide a reliable and valid outcome of free-living walking behavior in PwMS [30]. The number found in this study was comparable to previous studies [11,31] while PwMS with mild ambulatory dysfunction made significant more steps than those with a higher disability degree [11,32].…”
Section: Discussionsupporting
confidence: 88%
“…The number of steps taken per day was previously shown to provide a reliable and valid outcome of free-living walking behavior in PwMS [30]. The number found in this study was comparable to previous studies [11,31] while PwMS with mild ambulatory dysfunction made significant more steps than those with a higher disability degree [11,32].…”
Section: Discussionsupporting
confidence: 88%
“…33 Other contributors to decreased PA in MS include fatigue, spasticity, balance difficulties, poor movement coordination, sensory problems, and depression. 34,35 Previous research has shown an inverse relationship between EDSS score and the amount of PA participation, where an increased level of disability as measured by the EDSS score corresponds to less time spent engaged in PA. 36,37 However, some of these studies were conducted with self-reported EDSS scores, 36,38 PatientDetermined Disease Steps scale scores, 39 or PA levels. 40 This study demonstrated that individuals diagnosed as having MS are able to spend time participating in PA of light intensity despite having increased disability as measured by EDSS scores.…”
Section: Discussionmentioning
confidence: 99%
“…That is, there is evidence that physical activity levels based on steps/day and/or accelerometer counts overall or minutes/day of MVPA decline as MS progresses as a disease [56]. Steps/day from motion sensors further have captured the effect of and recovery from a relapse in persons with MS [80,81]. This suggests that the output from motion sensors may have clinical utility in MS for monitoring disease progression and activity.…”
Section: Five-year View: What Is Next?mentioning
confidence: 99%